2021
DOI: 10.2147/cia.s318525
|View full text |Cite
|
Sign up to set email alerts
|

A Minimally Invasive Technique Using Cortical Bone Trajectory Screws Assisted by 3D-Printed Navigation Templates in Lumbar Adjacent Segment Degeneration

Abstract: Revision surgery for adjacent segment degeneration (ASD) commonly requires exposing and removing the original fixation. To minimize trauma and to reduce the operation time and blood loss, we introduced a minimally invasive lumbar revision technique using cortical bone trajectory (CBT) screws assisted by three-dimensional (3D)-printed navigation templates. Methods: From April 2017 to October 2019, 18 patients with ASD underwent revision surgery with CBT screws assisted by 3D-printed templates in our hospital. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(37 reference statements)
0
2
0
Order By: Relevance
“… 2021 He K et al. [ 100 ] Clin Interv Aging 18 CBT screws for revision surgery of ASD Revision surgery for ASD with CBT screws assisted by 3D-printed navigation templates has satisfactory clinical efficacy with the advantages of a short operation time, a small incision, and less blood loss. 2020 Matsukawa K et al.…”
Section: Basic Types and Clinical Applications Of Orthopedic 3d Print...mentioning
confidence: 99%
See 1 more Smart Citation
“… 2021 He K et al. [ 100 ] Clin Interv Aging 18 CBT screws for revision surgery of ASD Revision surgery for ASD with CBT screws assisted by 3D-printed navigation templates has satisfactory clinical efficacy with the advantages of a short operation time, a small incision, and less blood loss. 2020 Matsukawa K et al.…”
Section: Basic Types and Clinical Applications Of Orthopedic 3d Print...mentioning
confidence: 99%
“…[ 97 ]. Subsequently, an increasing number of authors have reported the use of guides in lumbar screw placement [ [98] , [99] , [100] ]. It offers a similar effect in the cadaveric study.…”
Section: Basic Types and Clinical Applications Of Orthopedic 3d Print...mentioning
confidence: 99%
“…The rate of screw loosening may increase if the original trajectory is reinserted using the same instrumentation as in the initial surgery [ 32 , 33 ]. The course of the disease from the initial lumbar fusion to ASD is generally very long, and the bone quality of such patients is decreased to varying degrees.…”
Section: Discussionmentioning
confidence: 99%